The Efficacy of Rule of Law Publicity Short Video Platforms in the Prevention of Medical Disputes Among Healthcare Professionals: A Propensity Score Analysis - Yi M; Cao Y; Wang J; Shi C; Cheng Y; Cao Y (Dove Medical Press, 2023)
Min Yi,1 Yuebin Cao,2 Jiangjun Wang,3 Chenyi Shi,1 Yalin Cheng,1 Yanlin Cao1 1Institute of Medical Information and Library, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100020, People's Republic of China; 2Health Commission of Hunan Province, Changsha, 410008, People's Republic of China; 3China-Japan Friendship Hospital, Beijing, 100029, People's Republic of ChinaCorrespondence: Yanlin Cao, Institute of Medical Information and Library, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 3 Yabao Street, Chaoyang District, Beijing, 100020, People's Republic of China, Tel +86-010-52328845, Email cao.yanlin@imicams.ac.cnBackground: Medical disputes are a recurrent and pressing issue in hospitals, posing significant challenges to the functioning of medical institutions. We aimed to investigate whether receiving rule of law publicity on short video platforms is relevant to preventing medical disputes among healthcare professionals.Methods: We collected the data from 37,978 medical professionals from 130 tertiary public hospitals. Participants were classified into two groups according to the presence of receiving rule of law publicity on short video platforms. A subgroup analysis was performed before and after propensity score analysis, and multiple logistic regression was used to identify risk factors for medical disputes.Results: Among all participants, 46.1% (17,506/37,978) experienced medical disputes. Before propensity score analysis, the prevalence of medical disputes among participants who received rule of law publicity on short video platforms was similar to that among participants who did not (P = 0.639). However, after propensity score analysis, participants who received the rule of law publicity on short video platforms did not show a benefit effect. These participants had a significantly higher rate of suffering from medical disputes than participants who did not receive publicity on this platform (P=0.020). Multiple logistic regression analysis confirmed that receiving the rule of law publicity through short video platforms (P=0.010) or MicroBlog (P = 0.016), and previously facing legal issues outside of medical work (P < 0.001) were risk factors for medical disputes; participating in legal training organized by hospitals (P=0.004) and the hospital rule of law being very good (P=0.045) were protective factors.Conclusion: Medical disputes are a common occurrence within the healthcare profession. However, using short video platforms to promote the rule of law is not an effective method to prevent disputes. Instead, healthcare professionals can benefit from participating in legal training and having a well-established rule of law within the hospital construct.Keywords: healthcare professionals, medical disputes, rule of law publicity, short video platforms, construction of hospital rule of law